HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN PERILAKU DIET RENDAH GARAM PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS MELINTANG - Agustina; Ardiansyah; Rezka Nurvinanda (Jurnal Ilmiah Keperawatan, 2023)
Background:This research is motivated by the phenomenon of hypertension which is a major health problem today that has spread throughout the world and is also one of the most common causes of death. Because high blood pressure cannot be transmitted from one person to another, it is a disease. non-infectious chronic..Objective: This study is to determine the relationship between family support and the influence of low-salt diet behavior on people with hypertension in the work area of the Melintang Pangkalpinang Health Center in 2023. Method:This type of research is descriptive correlation with a cross sectional approach. Based on calculations using the formula above, the result is a sample size of 96.6, from this calculation it is rounded up to 97 samples. Added 10% of the total sample so that the results obtained were 108 respondents Results:These results indicate that based on the chi-square statistical test in this study, a p-value = 0.000 <0.05 This shows that there is a relationship between family support and adherence to low salt diet behavior in hypertension sufferers. Conclusion:There is a relationship between emotional, informational, instrumental, and assessment family support with adherence to low salt diet behavior in hypertension sufferers. Then adherence to a low-salt diet in the majority of respondents was in the obedient category, namely 84 people (77.8%), and 24 people (22.2%) did not comply.